Gender, Age And Somatotypical Characteristics Of The Hepatobiliary System (Literature Review). - Radjabov Akhtam Boltaevich; Babanazarov Umid Turobkulovich (Genius Journals, 2025)
This article presents a comprehensive analysis of the anatomical and physiological features of the hepatobiliary system, considering gender, age, and somatotypic factors. Current data on the morphometric parameters of the liver, pancreas, bile ducts, and spleen in various patient groups are discussed. Normative organ size indicators and their variations depending on age, gender, and body type are reviewed. Special attention is given to the capabilities of ultrasound diagnostics as the primary non-invasive method for visualizing structural changes in the hepatobiliary system. The importance of individualized anatomical assessment in interpreting ultrasound data and in early diagnosis of various pathologies is emphasized.
Keywords: hepatobiliary system; liver; pancreas